LISTENING COMPREHENSION STRATEGIES EMPLOYED BY INDONESIAN EFL STUDENTS: LESSON LEARNED FROM INDONESIAN ISLAMIC HIGHER EDUCATION - Fetriani, Fetriani; Baluqiah, Kiagus; Fransiska, Meta (Research And Innovation In Language Learning (RILL), 2020)
The objective of this research is to know the strategies in acquiring listening comprehension used by English students in English classes of Islamic university in Bengkulu, Indonesia.  The data of the research included questionnaire and interview the result of this research, there were two strategies in acquiring listening: First in direct strategies they were memory, cognitive and compensation strategies. Second in indirect strategies they are metacognitive, affective and social strategies. Especially in direct strategies, memory was the most strategy was chosen by students in the second semester. Indirect strategies, social was the most strategy was chosen by student. So the most strategies used by English students are memory and social strategy. The objective of this research is to know the strategies in acquiring listening comprehension used by English students in English classes of Islamic university in Bengkulu, Indonesia.  The data of the research included questionnaire and interview the result of this research, there were two strategies in acquiring listening: First in direct strategies they were memory, cognitive and compensation strategies. Second in indirect strategies they are metacognitive, affective and social strategies. Especially in direct strategies, memory was the most strategy was chosen by students in the second semester. Indirect strategies, social was the most strategy was chosen by student. So the most strategies used by English students are memory and social strategy